HUBUNGAN PARTISIPASI PUBLIK TERHADAP PENGEMBANGAN DESA WISATA : Suatu Penelitian Tentang Hubungan Partisipasi Publik Terhadap Pengembangan Desa Wisata Di Desa Genilangit, Kecamatan Poncol, Kabupaten Magetan Tahun 2021 - Kharisma Meypurba Ningrum; Bambang Martin Baru; Harianto (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The process of public participation involves the general public taking part in decision-making. Policy, strategy, communication, media for social issues, and social treatment all benefit from participation. It is known that a local initiator and members of the community worked together to create the Genilangit Tourism Park in the Poncol District of the Magetan Regency. With this in mind, every activity and program that runs in various capacities must be included in the construction of a public tourism village. The potential for development can be battled for and reaped jointly with the help of the community. In this study, it is determined how public involvement will affect the creation of a tourist village in 2021 in Genilangit Village, Poncol District, Magetan Regency. Because this tourist destination is growing quickly and is in high demand from visitors outside the city, it was chosen as a research subject. An explanatory quantitative methodology was used in this investigation. 100 respondents were given questionnaires to complete in order to gather the research's findings. According to the study's findings, there was a STRONG link between the two variables, with a result of 0.504 indicating that the association's strength was between 0.5 and 0.75. In this instance, it is possible to deduce that Ho is refused whereas Ha is approved, indicating a connection between community involvement and the creation of a tourist town in Genilangit Village., Poncol District, Magetan Regency, 2021.